Islamic Family Law Reform: Early Marriage and Criminalization (A Comparative Study of Legal Law in Indonesia and Pakistan) - Abubakar, Fatum (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2019)
In this paper I want to compare of legal law in Indonesia and Pakistan about early marriage. In Indonesia, marriage law No. 1/ 1974 explained that the limit of age of marriage is sixteen (16) years for women and nineteen (19) years for men. In Pakistan, after the 1961 MFLO amendment, Pakistan established the minimum age of marriage under the Child Marriage Restraint Act, 1929, is eighteen (18) years for men and sixteen (16) years for women. In addition to Law No. 1 of 1974, in Indonesia, the KHI is clearly repeating Article 15 Paragraph (2), for candidates who have not reached the age of 21 years, they must obtain permission as provided in Article 6 Paragraph (2), (3), (4), and (5) of Law No. 1 year 1974. Otherwise, in Indonesia this regulation is slower than other perversions country that I mention. The questions in this paper are; first, why does the legislation of Indonesia provides dispensation of marriage in the Court for prospective couples under the age of marriage? Second, why does Pakistan’s legislation give prison sanctions and penalties for married couples under the age of marriage? Thirdly, why does the legislation of Indonesia and Pakistan implement different determination of law for early marriage? The conclusion; if both prospective brides are still below the minimum age for marriage, the parents of the two brides-to-be may submit a marriage dispensation in a religious court. Dispensation of this marriage is regulated in Minister of Religious Affairs Regulation No. 3 year 1975, specifically for people who are Moslems. This matter the marriage law also provides an outlet as a solution if the minimum age requirement is not met. Otherwise, In Pakistan, Historically; the marriage of children is in conflict between those who feel established and those who want change by reforming their family law. So, MFLO 1961 came out of the outcome of the change of the Child Marriage Restraint Act 1929 to sanction marriage with fines and imprisonment for married couples who are married under the minimum age set for marriage. Even sanctions are given for parents, guardian, and marriage organizers as well as even more than the sanctions given to his son. Even if the renewal of Islamic law in the Indonesia have been done. Indonesia is somewhat late in doing Islamic law reform than Pakistan.